2016
DOI: 10.1007/s00395-016-0594-x
|View full text |Cite
|
Sign up to set email alerts
|

Transition in the mechanism of flow-mediated dilation with aging and development of coronary artery disease

Abstract: In microvessels of patients with coronary artery disease (CAD), flow-mediated dilation (FMD) is largely dependent upon the endothelium-derived hyperpolarizing factor HO. The goal of this study is to examine the influence of age and presence or absence of disease on the mechanism of FMD. Human coronary or adipose arterioles (~150 µm diameter) were prepared for videomicroscopy. The effect of inhibiting COX [indomethacin (Indo) or NOS (L-NAME), eliminating HO (polyethylene glycol-catalase (PEG-CAT)] or targeting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
59
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 42 publications
(63 reference statements)
4
59
1
Order By: Relevance
“…Based on those observations, the authors concluded that endothelium‐dependent dilation of microvessels was maintained after heavy resistance exercise in exercise‐trained individuals but not in sedentary subjects and that the mediator of endothelium‐dependent dilation of these vessels changes from NO prior to exercise to H 2 O 2 after heavy resistance exercise or exposure to high pressure alone. Finally, as noted in a recent review by Beyer et al ., the mechanisms of flow‐mediated dilation in human coronary arteries can change not only with age (from prostacyclin in youth to NO in adulthood) but also with coronary artery disease (H 2 O 2 ‐mediated). Taken together, the results of earlier studies and those of the present study by Park et al .…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Based on those observations, the authors concluded that endothelium‐dependent dilation of microvessels was maintained after heavy resistance exercise in exercise‐trained individuals but not in sedentary subjects and that the mediator of endothelium‐dependent dilation of these vessels changes from NO prior to exercise to H 2 O 2 after heavy resistance exercise or exposure to high pressure alone. Finally, as noted in a recent review by Beyer et al ., the mechanisms of flow‐mediated dilation in human coronary arteries can change not only with age (from prostacyclin in youth to NO in adulthood) but also with coronary artery disease (H 2 O 2 ‐mediated). Taken together, the results of earlier studies and those of the present study by Park et al .…”
mentioning
confidence: 76%
“…Finally, as noted in a recent review by Beyer et al ., the mechanisms of flow‐mediated dilation in human coronary arteries can change not only with age (from prostacyclin in youth to NO in adulthood) but also with coronary artery disease (H 2 O 2 ‐mediated). Taken together, the results of earlier studies and those of the present study by Park et al . highlight the complexities associated with age‐related impairment in vascular function and generate interesting questions about potential changes in the mediators and mechanisms of endothelium‐dependent dilation with age, disease and exercise training.…”
mentioning
confidence: 76%
“…We extend these findings and demonstrate that acutely elevated levels of LPA disrupt endothelium‐dependent FID in human arterioles by shifting the mechanism away from NO to mtH 2 O 2 . There was a noticeable improvement in dilation at lower pressure gradients after L‐NAME treatment (Figure B), which could potentially be ascribed to elimination of uncoupled eNOS‐derived reactive nitrogen/oxygen species, which scavenge the dilatory ROS (Yang et al ., ) or the fact that quenching any remaining NO releases the block on mtH 2 O 2 (Beyer et al ., ). LPA significantly reduced dilation to ACH, potentially by increasing intracellular ROS, which can compromise endothelial NO bioavailability.…”
Section: Discussionmentioning
confidence: 97%
“…A.U.arbitrary units, (n) indicates number of subjects. (Beyer et al, 2017). LPA significantly reduced dilation to ACH, potentially by increasing intracellular ROS, which can compromise endothelial NO bioavailability.…”
Section: Figurementioning
confidence: 93%
“…[1][2][3] In its primary role, TERT acts in the nucleus to maintain telomere length, stabilizing DNA. Gutterman and his colleague, Dr Andreas Beyer, found that TERT unexpectedly plays an additional role outside the nucleus.…”
mentioning
confidence: 99%